The use of cerium oxide nanoparticles in liver disorders: A double‐sided coin?. Issue 3 (13th January 2022) - Attia, Noha; Rostom, Dina M.; Mashal, Mohamed
Abstract: Being recognized as the first antioxidant nanoparticles (NPs) proposed for medicine, cerium oxide NPs (CeO2 NPs) have recently gained tremendous attention for their vast biomedical applications. Nevertheless, inconsistent reports of either medical benefits or toxicity have created an atmosphere of uncertainty hindering their clinical utilization. Like other NPs advocated as a promising protective/therapeutic option, CeO2 NPs are sometimes questioned as a health threat. As CeO2 NPs tend to accumulate in the liver after intravenous injection, liver is known to represent the key tissue to test for their therapeutic/toxicological effects. However, more research evidence is still needed before any conclusions can be elicited about the mechanisms by which CeO2 NPs could be harmful or protective/therapeutic to the liver tissue. A proper understanding of such discrepancies is warranted to plan for further modifications to mitigate any side effects. Therefore, in this MiniReview, we tried to demonstrate the two sides of the same coin, CeO2 NPs, within the liver context. As well, we highlighted a few promising strategies by which the negatives of CeO2 NPs could be diminished while enhancing all the positives.